The Influence of Age and Cardiorespiratory Fitness on Bioactive Lipids in Muscle. (25th September 2018) - Søgaard, Ditte; Baranowski, Marcin; Dela, Flemming; Helge, Jørn Wulff
Abstract: Reduced insulin sensitivity is observed with aging and often explained by decreased physical activity. The mechanisms involved are not clarified, but bioactive lipids may play a role. We aimed to evaluate the influence of age and cardiorespiratory fitness on ceramide and diacylglycerol content in muscle and key proteins in lipid metabolism and insulin signaling. Healthy males were stratified by age into trained and untrained groups including 27 young (23.2 ± 0.3 years) and 33 aged (65.2 ± 0.6 years). Maximal oxygen uptake and body composition were measured and fasting blood samples and muscle biopsies obtained. Muscle ceramide and diacylglycerol were determined by thin-layer and gas–liquid chromatography and proteins by western blotting. We show that HOMA-IR was higher and VO2 peak lower in aged compared with young. Total, saturated, C16:0 and C18:0 ceramide content were lower in muscle from aged compared with young. Intramuscular C18:1n9 and C20:4n6 content were higher in trained versus untrained. Content of total unsaturated and C16:1n7 diacylglycerol fatty acids were higher and C24:0 lower in muscle of aged versus young. Cardiorespiratory fitness had no impact on total diacylglycerol content. In conclusion, these data argue against intramuscular ceramide or diacylglycerol accumulation as driver of age-related insulin resistance in lean individuals.